2020
DOI: 10.1101/2020.03.02.956961
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Switching secretory pathway direction for organelle acquisition in plants

Abstract: 26Eukaryotic cells acquired novel organelles during evolution through mechanisms that 27 remain largely obscure. The existence of the unique oil body compartment is a 28 synapomorphy of liverworts that represents lineage-specific acquisition of this organelle 29 during evolution, although its origin, biogenesis, and physiological function are yet 30 unknown. We found that two Syntaxin 1 paralogs in the liverwort, Marchantia 31 polymorpha, are distinctly targeted to forming cell plates and the oil body, suggest… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…However, the presence of a limited number of oil bodies in the mutants Article suggests that other transcriptional regulators could be relevant along with MpC1HDZ. For example, recently, MpERF13, a TF from the AP2-ERF family, was also shown to be involved in oil body cell differentiation [20].…”
Section: Mpc1hdz-mediated Depletion Of Oil Bodies Affects Arthropod Herbivorymentioning
confidence: 99%
See 1 more Smart Citation
“…However, the presence of a limited number of oil bodies in the mutants Article suggests that other transcriptional regulators could be relevant along with MpC1HDZ. For example, recently, MpERF13, a TF from the AP2-ERF family, was also shown to be involved in oil body cell differentiation [20].…”
Section: Mpc1hdz-mediated Depletion Of Oil Bodies Affects Arthropod Herbivorymentioning
confidence: 99%
“…Pfeffer, who gave oil bodies their name (O ¨lko¨rper), noted they were membrane bound [17], and later studies confirmed a single membrane [18,19], in which isoprenoid biosynthesis enzymes are localized [16]. A recent report showed that the oil body membrane results from the fusion of secretory vesicles that requires a cyclic switching of the secretory pathway regulated by MpERF13 transcription factor [20].…”
Section: Introductionmentioning
confidence: 99%